THE INFLUENCE OF BEACH BALL STRATEGY TOWARD READING NARRATIVE TEXT - Asti Veto Mortini (Universitas PGRI Palembang, 2019)
AbstractThe objective of this research is to find out was any significant influence in learning reading narrative text between the tenth grade students of Madyatama Vocational High School of Palembang who are taught through Beach Ball strategy and those who are not. This research used quasi experimental method. Two groups were as the sample; experimental and control groups. Data was collected through written tests; pretest and posttest. It was analyzed them using independent sample test. The result showed t-obtained was 5.800. It was higher than t-table (2.004) at the significance level p<0.05 in two tailed testing with df=54. It means that there was a significant influence between the tenth grade students of state Senior High School 4 of Palembang in learning reading narrative text who are taught through Beach Ball strategy and those who are not.Keywords: Beach Ball Strategy, Reading, Narrative Texts